Tracked Changes. Specification for installation, exchange, relocation, maintenance and removal of gas meters with a maximum capacity not exceeding 6 mu3/h. Medium pressure (2nd family gases) Part 2, (31st January 2020) - British Standards Institution,
No abstract available